2022
DOI: 10.1590/2177-6709.27.5.e2220325.oar
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of products for bleaching and whitening under orthodontic brackets

Abstract: Introduction: Many patients wearing orthodontic appliances request alterations in the shade of their teeth during orthodontic treatment. Objective: This study aimed to evaluate the efficacy of different products for bleaching and whitening under orthodontic brackets. Methods: Seventy bovine incisors were randomly divided into five groups (n = 14): C) non-whitening toothpaste (control); WTsi) hydrated silica whitening toothpaste; WThp) 2% hydrogen peroxide whitening toothpaste; OB) in-office bleaching; and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…These results are probably related to the increase in the skeletal measurements, which despite not having shown statistically significant differences, were numerically greater in the MARPE group and corroborated with previous findings 17,18,24 . Although the skeletal measurements did not present a statistically significant change, the values obtained in the present study for the MARPE group for the interjugular distance (J‐J: 2.77 mm) and nasal base (NB‐NB: 2.82 mm) are in accordance with the values described in the literature 19,29–31 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are probably related to the increase in the skeletal measurements, which despite not having shown statistically significant differences, were numerically greater in the MARPE group and corroborated with previous findings 17,18,24 . Although the skeletal measurements did not present a statistically significant change, the values obtained in the present study for the MARPE group for the interjugular distance (J‐J: 2.77 mm) and nasal base (NB‐NB: 2.82 mm) are in accordance with the values described in the literature 19,29–31 …”
Section: Discussionsupporting
confidence: 92%
“…17,18,24 Although the skeletal measurements did not present a statistically significant change, the values obtained in the present study for the MARPE group for the interjugular distance (J-J: 2.77 mm) and nasal base (NB-NB: 2.82 mm) are in accordance with the values described in the literature. 19,[29][30][31] The transverse increment of 3.26 mm at the maxillary interfirst molar distance in the group treated using AEA observed in the present study (Table 4) is similar to the values observed in a previous study 10 and a clinical report. 9 The CBCT scans were obtained using different devices in each group so that there were different voxels (AEA group: 0.25 group; MARPE group: 0.08).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…(3) no carious lesions or restorations; (4) no enamel decalcifications; (5) no severe plaque ac-cumulation; (6) no history of bleaching; (7) no history of daily use of chlorohexidine mouth rinses; (8) medically and mentally fit with no disabilities; and (9) availability of a CBCT image showing at least the anterior maxilla. The teeth examined were maxillary centrals (#11), laterals (#22), canines (#13), and first premolars (#24).…”
Section: Subjects and Teethmentioning
confidence: 99%